2021
DOI: 10.3390/biomedicines9111519
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate (S1P) in the Peritoneal Fluid Skews M2 Macrophage and Contributes to the Development of Endometriosis

Abstract: Sphingosine 1-phosphate (S1P), an inflammatory mediator, is abundantly contained in red blood cells and platelets. We hypothesized that the S1P concentration in the peritoneal cavity would increase especially during the menstrual phase due to the reflux of menstrual blood, and investigated the S1P concentration in the human peritoneal fluid (PF) from 14 non-endometriosis and 19 endometriosis patients. Although the relatively small number of samples requires caution in interpreting the results, S1P concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…S1P which is abundant in blood constituents, principally in erythrocytes and platelets, has an important role in the proliferation of endometriotic cells [44]. High levels of S1P in fact have been found in the peritoneal environment of women suffering of endometriosis, showing the capability to induce differentiation of macrophages into CD163 + M2 type, which secretes pro-inflammatory cytokines such as IL-6, COX-2, and TGF-β contributing to the inflammation and fibrosis underlying these lesions [45].…”
Section: Ovarian Endometriosis (Oma)mentioning
confidence: 99%
“…S1P which is abundant in blood constituents, principally in erythrocytes and platelets, has an important role in the proliferation of endometriotic cells [44]. High levels of S1P in fact have been found in the peritoneal environment of women suffering of endometriosis, showing the capability to induce differentiation of macrophages into CD163 + M2 type, which secretes pro-inflammatory cytokines such as IL-6, COX-2, and TGF-β contributing to the inflammation and fibrosis underlying these lesions [45].…”
Section: Ovarian Endometriosis (Oma)mentioning
confidence: 99%
“…[ 105 ] 1.IL-17A could induce macrophage recruitment and M2 polarization Ono et al. [ 106 ] The sphingosine 1-phosphate concentration was greatly increased in peritoneal fluid from patients with endometriosis Sphingosine 1-phosphate induced M2 polarization Itoh et al. [ 107 ] 1.…”
Section: The Role Of Macrophages In Endometriosismentioning
confidence: 99%
“…The elevated EV-LGMNP1 induced M2 polarization, and serum increased EV-LGMNP1 suggested that EV-LGMNP1 may have clinical implications [ 104 ]. Abnormally elevated components in peritoneal fluid may also be inducers of M2 polarization, such as IL-17A and sphingosine1-phosphate (S1P) [ 105 , 106 ]. M2 macrophages accelerated ectopic ESCs proliferation through stat3 activation [ 107 ], and contributed to the angiogenesis through producing VEGF-A and TGFβ1 [ 108 ].…”
Section: The Role Of Macrophages In Endometriosismentioning
confidence: 99%
“…M2 MΦ has already been proven to contribute to angiogenesis through the production of TGF-β1, thus leading to the worsening of endometriosis. The excessive presence of COX-2 expressing MΦ, in patients with endometriosis, might prevent the deletion of refluxed menstrual blood, which causes high S1P levels during the non-menstrual phase [ 48 ]. Taken all together, these results revealed that MΦ, in patients with endometriosis, could be stuck in a “vicious cycle” since the phagocytosis of MΦ is decreased because of the increased expression of COX-2.…”
Section: S1p Pathway and Common Gynecologic Disorders (Gds)mentioning
confidence: 99%
“…Therefore, breaking up this cycle (i.e., by reducing S1P levels via inhibition/neutralization of SK) could be a potential therapeutic target. Meanwhile, a confirmatory in vivo study indicated that administration of S1P increased the dimension of the endometriotic-like lesion in a mouse model of endometriosis [ 48 ].…”
Section: S1p Pathway and Common Gynecologic Disorders (Gds)mentioning
confidence: 99%